2020
DOI: 10.1055/a-1091-8831
|View full text |Cite
|
Sign up to set email alerts
|

Trichothecenes from an Endophytic Fungus Alternaria sp. sb23

Abstract: Three new (alterchothecenes A – C, 1 –3) and 3 known (4 –6) trichothecenes, along with 9 known compounds (7 –15), were isolated from the culture of Alternaria sp. sb23, an endophytic fungus separated from the root of Schisandra sphenanthera Rehd. et Wils. Their structures were elucidated by spectroscopic analyses, and the absolute configurations of 1–3 were determined through comparison of the experimental electronic circular dichroism (ECD) spectra and optical rotations with similar analogues. In vitro cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…SZMC 23772 Hypericum perforatum Antimicrobial activity [ 60 ] Alternaria sp. sb23 Schisandra sphenanthera Anticancer activity [ 223 ] Alternaria sp. LV52: Cystoseira tamariscifolia Anticancer activity [ 224 ] A. alternata Paeonia lactiflora Anticancer activity [ 225 ] A. alternata MGTMMP031 Vitex negundo Anticancer activity [ 226 ] A. altenata Lithospermum Officinale Antioxidant activity [ 227 ] A.alternata Picrorhiza kurroa Antioxidant and antimicrobial activities [ 185 ] A.alternata Melissa officinalis Anticancer activity [ 228 ] A.alternata Ziziphus spina-christi Antimicrobial and antioxidant activities [ 186 ] A. brassicicola Terminalia arjuna Anticancer activity [ 229 ] A.Destruens Calotropis gigantean Antimicrobial, antibiofilm, antidiabetic activities [ 230 ] …”
Section: Biomedical Applications Of Fungal Endophytesmentioning
confidence: 99%
“…SZMC 23772 Hypericum perforatum Antimicrobial activity [ 60 ] Alternaria sp. sb23 Schisandra sphenanthera Anticancer activity [ 223 ] Alternaria sp. LV52: Cystoseira tamariscifolia Anticancer activity [ 224 ] A. alternata Paeonia lactiflora Anticancer activity [ 225 ] A. alternata MGTMMP031 Vitex negundo Anticancer activity [ 226 ] A. altenata Lithospermum Officinale Antioxidant activity [ 227 ] A.alternata Picrorhiza kurroa Antioxidant and antimicrobial activities [ 185 ] A.alternata Melissa officinalis Anticancer activity [ 228 ] A.alternata Ziziphus spina-christi Antimicrobial and antioxidant activities [ 186 ] A. brassicicola Terminalia arjuna Anticancer activity [ 229 ] A.Destruens Calotropis gigantean Antimicrobial, antibiofilm, antidiabetic activities [ 230 ] …”
Section: Biomedical Applications Of Fungal Endophytesmentioning
confidence: 99%
“…New trichothecene derivatives with a 1, 2-diol moiety at C-12 and C-13, alterchothecenes A-C (166-168), were isolated from Alternaria sp. sb23 bearing a 12, 13epoxytrichothec-9-ene ring moiety (Gao et al, 2020). Spectra data analysis of NMR, DEPT, and HSQC suggested that 167 is 8-dihydrogeneated derivatives and 168 is 13-acetylated derivatives of 166 respectively (Gao et al, 2020).…”
Section: Terpenesmentioning
confidence: 99%
“…sb23 bearing a 12, 13epoxytrichothec-9-ene ring moiety (Gao et al, 2020). Spectra data analysis of NMR, DEPT, and HSQC suggested that 167 is 8-dihydrogeneated derivatives and 168 is 13-acetylated derivatives of 166 respectively (Gao et al, 2020). Similarly, (1R,5R,6R,7R,10S)-1,6-Dihroxyeudesm-4(15)-ene ( 169) is a new sesquiterpenoid isolated from Alternaria alternate .…”
Section: Terpenesmentioning
confidence: 99%
“…Currently, approximately 200 members of the trichothecene family have been identified [ 8 ]. Trichothecenes are also a source of contamination in food, which could induce a series of acute and chronic symptoms, such as hypotension, anemia and so on [ 9 ]. Nevertheless, some trichothecenes have also been reported to exhibit antifungal, antimalarial, antiviral and phytotoxic activities [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trichothecenes are also a source of contamination in food, which could induce a series of acute and chronic symptoms, such as hypotension, anemia and so on [ 9 ]. Nevertheless, some trichothecenes have also been reported to exhibit antifungal, antimalarial, antiviral and phytotoxic activities [ 9 , 10 , 11 ]. The biological investigation of the five compounds suggested that all of them exhibited cytotoxicities against Huh-7 cells and MRMT-1 cells.…”
Section: Introductionmentioning
confidence: 99%